Sistemas de aproveitamento de carcaças e esterco de suínos nas granjas no Oeste do Paraná - Bender, Sílvio (2022)
In Brazil, the current swine production system is characterized by intensive, where there is a high density of animals and volume of waste, mostly concentrated in small rural properties. The production of biomethane from swine manure has grown in recent years in Brazil and worldwide. This increase causes impact and the need to change legislation and alternatives based on research to improve techniques and mechanisms for the use of waste, in a sustainable manner and with proper disposal. In the west of Paraná, there has been growing interest in the development of the potential for generating biogas and electricity from swine waste by swine farmers, as well as by entrepreneurs of bioenergy production plants. There are three Plants that are in operation where they develop in this region the production of biogas, electricity and biofertilizer, using swine waste as one of the raw materials. We highlight the systems most used by pig farmers on farms, with the treatment of waste, manure and pig carcasses on farms and the products generated with proper processing, such as biogas and biofertiizante. Thus, this work will address the ways of use of waste generated by pig farming projects, based on environmental legal aspects, doctrinal references to the subject, research in the Environmental Management System - SGA and field research which includes, among other points, licensed pig farming activities and those that are in process of licensing by the Instituto Água e Terra. The SGA-IAT, as a research tool, presents the Environmental Control Plans for licensed pig farming activities with the treatments used in each project and the proper use of the waste generated. In addition to the elaboration of a booklet called “Booklet: Systems for the use of carcasses and swine manure on farms”,. which will address in a simplified way the advantages and disadvantages of treatment systems and use of these residues on farms, seeking to make pig farmers aware of the importance of technologies for an increasingly sustainable production on rural properties.